Experimental simple shear study of composite soil with cemented soil core. Issue 8 (14th September 2019) - Liu, Feiyu; Zhu, Kai; Hu, Xiuqing; Fu, Hongtao; Feng, Dong
Abstract: Cement soil mixing piles are an effective treatment method for marine soft clay. To investigate the static and dynamic characteristics of the composite soil with cemented soil core, a series of experiments are carried out by using the cyclic simple shear test. The result shows that, the static shear strain showed strain hardening, cemented soil core can improve static shear strength of composite soil, vertical stress can enlarge reinforcement of cemented soil core. The tendency of strain development of composite soil with different area replacement ratios under cyclic loading is the same as that of pure clay, existing critical cyclic stress ratios corresponding to different area replacement ratios. In addition, improving area replacement ratio can increase cyclic strength. At same time, adding of cemented soil core does not change shape of hysteresis curve compared with it for clay either. Moreover, cemented soil core can also obstruct stiffness softening. Through regression analysis of the experimental data, relationship between cyclic number and soil softening index is proved to be linear. The results can give a reference for the dynamic characters of the marine soft clay foundation with cement soil mixing piles.